Bairro brincante : estudo sobre entrecruzamentos de socialidades constitutivas de um bairro de Juazeiro do Norte-CE - Feitosa, Antonio Lucas Cordeiro (2020)
This doctoral thesis is a sociocultural study on the ways some socialities crisscross in the making of João Cabral neighborhood, in the city of Juazeiro do Norte, Ceará state, Brazil. The recurring use of categories “periphery”, “traditional culture” and “violence” in narratives about the neighborhood was noted through field research conducted from 2017 to 2020, being common in the city and region its classification as “the most, or one of the most violent neighborhoods”, “peripheral”, “source/cradle of traditional culture”. At the same time, cultural practices identified as “traditional culture” (in Portuguese, “cultura popular”, such as the reisado, guerreiro, maneiro-pau, bacamarte, lapinha and the banda cabaçal, a band with musical instruments made of gourds) are deemed as a means of “taking kids and youth off the streets away from the world of crime”, “social work with youth”, and “improving the neighborhood reputation”. The dynamics of urban social conflicts in many Brazilian cities, on the other hand has pervaded the universe of “traditional culture”, especially the play of reisado, performed for the Christian holiday of Epiphany or Day of the Kings. In the days of playing reisado, many young men are dressing up as “the beast” (cão), using a long overall, whip and a mask. The beasts – os cão, as they are locally called – arouse both fear and admiration. In the local field of “traditional culture”, however, they have accused of belonging to criminal factions, of committing crimes, and creating disturbance with reisado groups of other neighborhoods Taking these empirical elements into account, this thesis’ objective consists of describing and analyzing the different connections and interlacements of the triad neighborhood (“periphery” – “traditional culture” – “violence”, questioning how, based on these connections, the João Cabral neighborhood is activated and produced through multiple fluxes. Through an ethnographic orientation, fieldwork research followed the “players” (brincantes) of traditional culture groups in their presentations in the João Cabral neighborhood and other parts of town either promoted by institutions or themselves. Along with these presentations and other events fieldwork notes and interviews with João Cabral residents and people associated with “players as well as documentary research on the neighborhood and “traditional culture” (magazines undergraduate papers, dissertations) were also used for analysis. The research makes possible to think the neighborhood through the crisscrossing of socialities, taking it as a multiplicity.